Effects of Interaction of Leucine and Valine on Growth, Body Wall Amino Acids Composition, and Digestive Ability of Sea Cucumber Apostichopus japonicus - Guofeng LU; Jiying WANG; Baoshan LI; Jingwei LIU; Tiantian HAO; Yongzhi SUN; Bingshan HUANG (Progress in Fishery Sciences)
Branched chain amino acids (BCAAs) are neutral amino acids containing branched aliphatic chains on the α-carbon, including leucine (Leu), isoleucine, and valine (Val), accounting for 18%–20% of the total amino acids in animal and plant proteins. BCAAs are essential amino acids for animal growth; however, they cannot be synthesized in animals and can only be obtained from the diet. BCAAs participate in the metabolism of protein, fat, and carbohydrates; promote intestinal development and intestinal amino acid transport; and improve the immune capacity of the body. However, the imbalance of BCAAs in diets leads to poor growth and metabolic disorders in animals. BCAAs have similar chemical structures and catabolic pathways and compete for the same amino acid transporters when passing through cell membranes, resulting in antagonism. Sea cucumbers (Apostichopus japonicus) have rich nutritional value and are an important seafood source in northern China.In recent decades, the study of amino acid nutritional requirements of aquatic animals mainly focused on individual amino acid requirements, and few studies focused on the interaction between amino acids with strong correlations, particularly BCAAs. At present, the interaction of BCAAs has been studied in species such as Chinook salmon (Oncorhynchus tshawytscha), Rainbow trout (Oncorhynchus mykiss), Channel catfish (Ictalurus punctatus), Tilapia GIFT (Oreochromis niloticus), and Tiger puffer (Takifugu rubripes); however, the results have been inconsistent.The purpose of this experiment was to study the interaction effect of Leu and Val on the growth, body wall composition, and digestive ability of sea cucumbers. In this experiment, white fishmeal, algae powder, and wheat flour were used as the primary protein sources, and fish oil and soybean lecithin were used as the main lipid sources to design a basic diet with crude protein and lipid contents of 18.10% and 2.80%, respectively. In a two-way experimental design, 0%, 1.06%, 2.34%, and 3.40% coated Leu and 0%, 1.74%, 2.50%, and 3.48% coated Val were added to the basic feed. Sixteen groups of isonitrogen and isolipid diets were prepared with four Leu levels (actual content: 1.00%, 1.50%, 2.10%, and 2.60%) and four Val levels (actual content: 0.65%, 1.40%, 1.70%, and 2.20%). A total of 960 healthy sea cucumbers with an initial average weight of 16.80±0.18 g were selected and randomly assigned to 48 cylindrical circulating buckets. They were divided into 16 experimental groups, with three replicates in each group and 20 sea cucumbers in each replicate. The feeding period was 60 d. Bait was fed once a day at a fixed time (16:00). The water was changed every 2 d, and a siphon was used to withdraw the residual bait and feces from the bottom of the bucket. The amount of water changed was 50% of the water level in the bucket. During the breeding period, the water temperature was 14–17 ℃, pH was 7.4–8.2, and dissolved oxygen was at least 6 mg/L. A low-light environment was maintained indoors.The results showed that the Leu and Val contents and their interaction significantly affected the weight gain (WG) and specific growth rate of sea cucumbers. When the Val content was 1.4%, the crude lipid contents of the body wall increased with increasing dietary Leu contents, and there was a synergistic effect between Leu and Val; the L1.0V1.4 group was significantly lower than the other groups. The interaction between Leu and Val significantly affected the Val, Met, Tyr, and Phe contents in the body wall of sea cucumbers. When the Leu content was 2.1%, the intestinal lipase and amylase activities first increased and then decreased with increasing dietary Val contents; the interaction between Leu and Val showed a synergistic and then antagonistic effect. The amylase activity reached a maximum value in the L2.6V1.4 group and was significantly higher than that in other groups. In conclusion, Leu and Val contents and their interaction significantly affected the growth performance, body wall amino acid composition, and digestive ability of sea cucumbers. Taking WG as the evaluation index, the ratios of Leu and Val in sea cucumber feed were 1.90 (Leu content was 2.6%, Val content was 1.4%).